What influences midwives in estimating labour pain?. (24th April 2012) - Williams, A.C. de C.; Morris, J.; Stevens, K.; Gessler, S.; Cella, M.; Baxter, J.
Abstract Background Clinicians' estimates of patients' pain are frequently used as a basis for delivering care, and the characteristics of the clinician and of the patient influence this estimate. Methods We studied pain estimation by midwives attending women in uncomplicated labour. Sixty‐six practising midwives of varied age, ethnicity and professional experience were asked to complete a trait empathy measure and then to estimate the maximum pain and anxiety experienced by six women whose filmed labour contractions they viewed. Additionally, they rated similarity to the labouring women in ethnicity, and described their beliefs about pain expression according to ethnicity. Results Midwife estimates of pain and anxiety were highly correlated. Longer professional experience was associated with lower pain estimates, while more births to the midwife herself was associated with higher pain estimates. A multiple regression model identified number of births to the midwife herself, and two components of empathy (perspective taking and identification), to be important in predicting midwife pain estimates for women in labour. Midwives expressed clear beliefs about women's expression of pain during labour according to ethnicity, but these beliefs were not consistent across midwives, even between midwives of similar ethnicity. Conclusion Midwives' personal characteristics can bias the estimation of pain in woman in labour and therefore influence treatment.